2021
DOI: 10.1016/j.adro.2020.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Lessons to Learn From a Successful Virtual Mock Oral Examination Pilot Experience

Abstract: oronavirus (COVID-19) has caused marked impact on graduate medical education for all medical specialties. Radiation Oncology and the American Board of Radiology have also had to rapidly adapt to converting education and examinations to virtual platforms. We describe our small pilot experience in transitioning our in-person mock oral examinations to a virtual platform. Survey-based assessment revealed excellent feedback regarding ease of use and educational usefulness. Our mock oral examinations pilot experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The positive-trending feedback of MOEs, especially those that are done virtually, in turn has led to an increased interest in the use of virtual platforms for administering MOEs. [7][8][9] MOEs are just one example of traditionally in-person events being shifted to a virtual paradigm due to the pandemic. Other educational forums, such as meetings and conferences, have had to adapt to the changing landscape of medical education, as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive-trending feedback of MOEs, especially those that are done virtually, in turn has led to an increased interest in the use of virtual platforms for administering MOEs. [7][8][9] MOEs are just one example of traditionally in-person events being shifted to a virtual paradigm due to the pandemic. Other educational forums, such as meetings and conferences, have had to adapt to the changing landscape of medical education, as well.…”
Section: Discussionmentioning
confidence: 99%
“…Virtual methods for medical trainee examination and assessment have become increasingly more prevalent due to COVID-19 and initial reviews have shown them to be adequate alternatives to traditional in-person educational paradigms. [8][9][10][11] The absence of major technological issues with administration of both the mock oral exam and recent vascular surgery oral board exam virtually is evidence of the practical utilization of alternative methods to in-person assessment and educational training. 6 As a result, some discrepancy between PDs and trainees in this study might represent different points of view instead of major issues with VMO per se.…”
Section: Limitationsmentioning
confidence: 99%
“…Past studies have shown the value and effectiveness of virtual MOEs in other medical fields such as general surgery, radiation oncology, and otolaryngology; however, no such study exists yet in plastic surgery. [7][8][9] Without the logistical constraints of physical coordination, we hypothesized that the virtual platform would improve and expand the MOE experience to include collaborative institutions while still approximating a board examination environment. Six clinical cases used for the MOE were solicited from faculty examiners, who do not normally conduct examinations for the American Board of Plastic Surgery (ABPS).…”
Section: Introductionmentioning
confidence: 99%
“…Among these was the online SOE, which is best suited for assessing interpretation skills. Justaniah et al have recently reported their experience with online oral examination for interventional radiology fellowship programme [ 7 ], while others have reported on online mock oral examinations in radiation oncology and in vascular surgery [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%